Association between inferior posterior staphyloma on choroidal vessels running patterns in healthy eyes - Hiroto Terasaki; Ryoh Funatsu; Koki Okamura; Naohisa Mihara; Hideki Shiihara; Takehiro Yamashita; Shozo Sonoda; Taiji Sakamoto (International Journal of Retina and Vitreous)
Abstract Background Effects of macular shape changes on the retina have been studied in pathologic myopia. However, whether there are individual differences in macular shape in non-pathologic myopia and the influence of macular shape on retinochoroidal disease in these eyes is not well known. A recently developed ultra-wide-field optical coherence tomography (UWF-OCT) has a wider imaging range and can be used to evaluate inferior posterior staphyloma (IPS). We aimed to investigate the effect of IPS on Haller vessel running patterns (HVRPs) in healthy eyes using UWF-OCT. Methods This single-center retrospective study included healthy subjects. UWF-OCT images of normal subjects were stretched vertically to enhance the macula's shape and classified into IPS (n = 16) and non-IPS (n = 113) groups with or without propensity score matching (PSM) for age, sex, and ocular axis length. The HVRPs were subjectively classified into symmetry, superior dominant, and inferior dominant. Differences in the proportions of the patterns between the two groups were compared using Fisher's exact test. Results In the non-IPS group, 65 (57.5%) individuals had a symmetric pattern of Haller's vessels, 32 (28.3%) had an upper-dominant pattern, and 16 (14.1%) had a lower-dominant pattern. In the IPS group, 14 eyes (87.5%) presented an upper dominant pattern, and 2 (12.5%) presented a symmetric pattern. There was a significant difference in vascular running patterns between the two groups (P < 0.001). After the PSM, a similar trend was confirmed. Conclusions The eyes with IPS are likely to have superior dominant HVRPs compared to the non-IPS group in healthy eyes. Macular shape may play a role in HVRPs, which are involved in the pathogenesis of retinochoroidal diseases.